2005
DOI: 10.1024/0301-1526.34.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The venous return simulator: an effective tool for investigating the effects of external compression on the venous hemodynamics – first results after thigh compression

Abstract: The venous return simulator computes lower limb hemodynamic parameters under static conditions. The good correlation existing between the VRS and the data obtained in a previous clinical study shows that this numerical approach could provide a useful means of predicting the hemodynamic consequences of compression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Calculation of hydraulic resistance requires an appreciation of the vessel geometry during collapse. Previous models (9–11) all used the buckling mechanics of thin‐walled, circular tubes subjected to uniform negative transmural pressure to model this. As a consequence, the calculation of flows induced by compression and the resulting wall shear stresses may not be realistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of hydraulic resistance requires an appreciation of the vessel geometry during collapse. Previous models (9–11) all used the buckling mechanics of thin‐walled, circular tubes subjected to uniform negative transmural pressure to model this. As a consequence, the calculation of flows induced by compression and the resulting wall shear stresses may not be realistic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous bioengineering efforts to quantify the effects of lower‐limb compression have involved reduced dimension models of venous networks (9–11). The relationship between the compressive force exerted by the device and the resulting deformation of the vein walls is a primary input to these models.…”
mentioning
confidence: 99%
“…IMP measurement was performed in the three deep compartments of the leg: soleus, gastrocnemius, and anterior tibial. The leggings had no effect on IMP during walking and running, but there was a significant increase in IMP in the standing position for low IPs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The main limitation, however, of Murthy's results was their improper use of Circaid Õ devices which, in our opinion, were applied too loosely in their study.…”
Section: For the Future: A Numerical Approach And Simulation By Finitmentioning
confidence: 98%
“…Fullana et al 21 created a venous return simulator to try to predict the effects of compression of the veins of the leg.…”
Section: Limitations Of the Three-dimensional Mri Modeling Of The Calfmentioning
confidence: 99%
“…Adding to the confusion, many details about how the cuff pressures were determined [initial pressure/tightness of cuff before inflation vs. final/target pressure – based on the original KAATSU philosophy ( Sato, 2005 )] are not clear or perhaps are not even reported. Fullana et al (2005) reported that only a pressure greater than 40mmHg would change venous diameter at thigh level. In addition, several studies confirmed that the accumulation of some by-products, such as lactate and hydrogen ions, might cause increased afferent signals from intramuscular metaboreceptors resulting in an increased growth hormone response ( Takarada et al, 2000a ; Goto et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%